Urban Water Management for Future Cities Technical and Institutional Aspects from Chinese and German Perspective - Köster, Stephan; Reese, Moritz; Zuo, Jian'e.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book features expert contributions on key sustainability aspects of urban water management in Chinese agglomerations. Both technical and institutional pathways to sustainable urban water management are developed on the basis of a broad, interdisciplinary problem analysis.
Preface -- PART I: Innovative Technologies and Implementation -- Chapter 1. Urban Stormwater Management and Sponge City Concept in China (Wu CHE) -- Chapter 2. Maintenance and Safety of Sponge City Infrastructure (Stephan Koester) -- Chapter 3. Future-oriented Strategic Planning of Wastewater Treatment Plants (Nina Manig, Maike Beier, Karl-Heinz Rosenwinkel) -- Chapter 4. Urban Drinking Water Challenges and Solutions: Energy Nexus (Shuming LIU) -- Chapter 5. Fostering Water Treatment in Eutrophic Areas: Innovative Water Quality Monitoring, and Technologies Minigating Taste & Odor Problems Demonstrated at Tai Hu (Christian Moldaenke, Stephan Küppers, Christian Staaks, Edmund Riehle, Tim aus der Beek, Andreas Tiehm) -- Chapter 6. Preventive and Customized Maintenance of Underground Water Infrastructure (Regina Haussmann, Fangfang ZHAO, Johannes Pinnekamp) -- Chapter 7. Implementing Real Time Control Systems to Minimize Emissions from the Sewer System (Michael Pabst) -- Chapter 8. Wetland Ecological Restoration Using Near-Natural Method (Chun YE) -- Chapter 9. Urban Flood Prevetion (Marc Illgen) -- Chapter 10. Urban Pipe Assessment Method and Its Application in Two Chinese Cities (Jina'e Zuo) -- Chapter 11. Special issues of Wastewater Management in China (Max Dohmann) -- PART II: Urban Water Governance -- Chapter 12. Urban Water Governance in Europa and in China: Key Challenges, Benchmarks and Approaches (Moritz Reese) -- Chapter 13. Sustainable Water Resource Management in China - Reflections from a Comparative Governance Perspective (Martin Grambow, Markus Disse, Ke Chen,Hannah Patalong & Hans-Dietrich Uhl) -- Chapter 14. Cross-boundary Evolution of Urban Planning and Urban Drainage Towards the Water Sensitive "Sponge City" (Meiyue Zhou. Stephan Koester, Jiane Zuo, Wu Che, Xianping Wang) -- Chapter 15. China's National Governance Framework for Urban Water Resource Management (Zhongmei Lv & Mingqing You) -- Chapter 16. Regional Water Policy in China - Problems and Approaches in theTaihu und Wuhan Regions (Liping Dai & Tianbao Qin) -- Chapter 17. German Water Protection Law with a Particular Focus on Waste Water Management (Wolfgang Köck) -- Chapter 18. Information, Participation and Public Control in Water Management & Water Infrastructure Development: the European Perspective (Silke R. Laskowski) -- Chapter 19. Economic Policies of Water Pollution Control and in the Taihu Lake Basin, China (Zhou Yunchun & Jun Bi) -- Chapter 20. The Eco-Compensation Mechanism in Tai Lake Watershed (Liping Dai & Tianbao Qin) -- Chapter 21. Economic Requirements and Instruments for Sustainable Urban Water Management - Comparative Review (Erik Gawel & Norman Bedtke) -- Chapter 22. Full Cost Accounting of Urban Water-Use (Guo-jun Song & Wen-cheng Gao) -- Chapter 23. The Economics and Management of Flood Risk in Germany (Volker Meyer & Reimund Schwarze).
Keywords: Urban ecology (Biology).; Sociology, Urban; Sustainability; Pollution; Water; Hydrology; Urban Ecology; Urban Sociology; Sustainability; Pollution; Water